Extended Retrosigmoid Approach for Cerebellopontine Angle Meningiomas: Operative Technique and Results—A Series of 28 Patients - Lynch, Jose Carlos; Pereira, Celestino; Welling, Leonardo; Gonçalves, Mariangela; Zanon, Nelci (Journal of Neurological Surgery Part B: Skull Base, 2018)
Background The purpose of this article is to describe our approach, surgical strategies, and results for resection of meningiomas located at cerebellopontine angle (CPA).Methods We retrospectively identified 28 patients with CPA meningiomas operated by the extended retrosigmoid approach. This approach incorporates a generous mastoidectomy and the sigmoid sinus exposure.Results The mean age was 33.8 years, with a follow-up of 12.5 years. Gross total removal (GTR) was achieved in 22 (78.5%) patients with low surgical mortality, acceptable morbidity, and recurrence rate of 7.1% (2 patients).Conclusion The extended retrosigmoid approach enhances the exposure of the CPA and posterior fossa cisterns and increases the surgical angle of maneuverability. This approach provides adequate access even to extensive CPA meningiomas, enabling, in most of cases, GTR to be safe and effective. The extended retrosigmoid approach used in this group of patients is an alternative to more extensive cranial base approaches.
Keywords: cerebellopontine angle meningiomas; extended retrosigmoid approach; meningiomas; posterior fossa meningiomas; sigmoid sinus